One View of the Current State of Understanding in Basal Ganglia Pathophysiology and What is Needed for the Future - Erwin B. Montgomery (Journal of Movement Disorders, 2011)
Deep Brain Stimulation (DBS), arguably, is the most dramatic development in movement disorders since the levodopa for Parkinson’s disease. Yet, its mechanisms of action of DBS are unknown. However, DBS related research already has demonstrated that current concepts of basal ganglia pathophysiology are wrong. Specifically, the notion that over-activity of the globus pallidus interna causes parkinsonism, the basis for the most current theories, is no longer tenable. The development of any new theory will be aided by an understanding of how current theories are wrong and why have these flawed theories persist. Many of the problems of current theories are more matters of inference, assumptions, presumptions, and the accepted level of ambiguity than they are of fact. Consequently, it is imperative that these issues be addressed. Just as the inappropriate use of a tool or method is grounds for criticism, methods of reasoning are tools that can be used inappropriately and should be subject to discussion just as misuse of any other tool. Thorough criticism can provide very important lesions though the process could be mistaken as harsh or personal; neither is the case here. At the least, such analyzes can point to potential pitfalls that could be avoided in the development of new theories. As will be discussed, theories are important for the development of therapies but perhaps most important, for the acceptance of new therapies, as was the case for the recent resurgence of interest in surgical therapies.